Infrared Spectral Studies of Diphenylamine - Srivastava, K.P.; Kumar, A. (Asian Journal of Chemistry, 2010)
The infrared spectra of diphenylamine were recorded to discuss the modes of vibrations, overtones and combination frequencies assuming the C2v point group symmetry. The investigations have been discussed with a view to examine the structural pattern and different nature of bonding in the molecule.